Does capability measurement enable aspiration during emergent adulthood? Examining 'Poverty Stoplight' as a poverty measurement and capability building instrument for youth in South Africa - Newell, Ashley Michelle (Graduate School of Business (GSB), 2020)
In South Africa, the majority of youth entering emerging adulthood find themselves in a protracted struggle to access further education, training or to secure their first decent job. The purpose of this multi-case study is to deepen the understanding of how capability measurement approaches and tools can empower marginalized youth to better understand their aspirations and map their way through emerging adulthood and out of poverty. This research aims to deepen the understanding of youth's experience utilizing 'Poverty Stoplight'; a poverty measurement and capability building instrument that utilizes a self-assessment survey and mentorship methodology. The researcher utilized a youth-focused participatory approach in conducting focus groups and in-depth one-on-one interviews across five marginalized communities in the Western Cape to gain insight into their experience using the tool, their ability to envision their future selves and develop their aspirations. What emerged from the data were insights into the youth's aspirations, the perceived enabling factors and impediments towards their aspirations and their experiences utilizing Poverty Stoplight. This process enabled youth to genuinely reflect and assess their situation, and have the opportunity to define their aspirations. Overall the Poverty Stoplight programme was experienced as empowering by participants, with several implications for the programme pertaining to data accessibility, communication, mentorship and solution sharing, as well as the importance of youth-specific participatory approaches. Aligned to this, the findings yielded several recommendations pertaining to providing support and enabling opportunities for emerging adults to realise their aspirations. Despite the limitations of this research, this study is relevant for stakeholders in South Africa and globally as it examines the critical issue of youth development, with a focus on the ability of young people to attain their aspirations. Further, it analyses the capability measurement approach as a means to ensuring young people can better understand and plot their way out of poverty, making the most of their individual capabilities and attributes within the broader structural and systemic challenges they face. This exploration of practical tools and methodologies being developed and utilized by pioneering organisations in the South African context provides empirical evidence of the merit of such approaches, with recommendations on how tools and approaches can even better serve the needs of youth. Further, longitudinal research is merited into the use of such capability measurement approaches to empower youth and the further use of participatory methodologies.